Impact of educational intervention on awareness regarding girl trafficking among adolescents. - Thapa, Bandana (2011)
ABSTRACT: The study entitled "Impact of Educational Intervention on Awareness regarding Girl Trafficking among Adolescents" was conducted to find out the impact of educational intervention in increasing awareness regarding girl trafficking among adolescent girls. Interventional study with pre experimental one group pre test post test design was used. Setting of study was public school situated in Nala, Kavrepalanchowk. The population of the study was the girl students of class 8, 9 and 10. Total of 90 girl students were taken by non-probability purposive sampling. The self administered semi structured questionnaire was administered to measure their awareness on girl trafficking before and after the educational intervention. Pre-test was done according to the convenience of students. The educational package prepared by the researcher was used for educational intervention. The educational intervention was conducted in 3 sessions for 3 consecutive days following the week of pretest. The Post test was done 2 weeks after the last interventional session with same instruments. The collected data were analyzed by using descriptive statistics such as frequency, percentage, mean, standard deviation, and inferential statistics like paired t-test at 0.05 level of significance. The findings revealed that the mean awareness of adolescents on girl trafficking was 39.94 with standard deviation 11.13 in pre test. The mean awareness in the post test was 63.92 with standard deviation 4.32. Hypothesis of the study ''There will be significant change in awareness regarding girl trafficking among adolescents after educational intervention'' was tested using paired t-test to measure the difference in awareness on girl trafficking among the adolescents between pre test and post test. P value was found to be 0.000 (<0.05) which reveals a significant difference between the two tests. Based on the study findings, it is concluded that educational intervention was found to be successful in increasing the awareness of adolescents on girl trafficking. Therefore, this type of educational program can be conducted to enhance awareness regarding girl trafficking in secondary school girl students.